Leptin − 2548 G > A gene polymorphism is associated with lipids metabolism and TGF-β alteration in sickle cell disease - Figueiredo, Camylla Vilas Boas (2016)
Brazilian National Council of Research (CNPq) (3065427/2007-5 and 484457/2007-1) (M.S.G.); the Foundation of Research and Extension of Bahia (FAPESB) (1431040053063 and 9073/2007) (M.S.G.); and MCD/CNPq/MS-SCTIE-DECIT (409800/2006-6), (M.S.G.).